Lower middle Darriwilian (Ordovician) graptolites and index conodonts from the Central Precordillera of San Juan Province, Argentina. (8th November 2017) - Serra, Fernanda; Feltes, Nicolás A.; Ortega, Gladys; Albanesi, Guillermo L.
Abstract : This study includes 3 localities from the Jáchal area in the Central Precordillera of San Juan Province, from north to south: the Oculta creek, Las Aguaditas creek, and Cerro La Chilca sections. We deal with the graptolite faunas and conodont index species recorded from units that overlie the carbonate San Juan Formation, spanning the lower part of the Los Azules, Las Aguaditas, and Gualcamayo formations in their respective areas. The index graptolites and associated species are reported, which enable the recognition of the Levisograptus dentatus Zone in the Central Precordillera. The presence of graptolites in the limestones from the top of the San Juan Formation at the Cerro La Chilca section is documented for the first time. The record of representatives of the Lenodus variabilis, Yangtzeplacognathus crassus, Eoplacognathus pseudoplanus, Histiodella, and Periodon lineages recognized in these units, linked with respective graptolite zones, provide precise information for global correlation purposes. The use of conodont and graptolite zones from different areas of the Central Precordillera enables the verification of the diachronous contact between the San Juan Formation and overlying units, which spans the lower to middle Darriwilian, in our investigated sections and classical localities previously documented.